Exploring the psychological values of the main character in Tere Liye's Burlian for Indonesian language learning - Aghna Joan Aqila; Adyana Sunanda (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aims to describe the personality structure of the main character in Burlian by Tere Liye based on Sigmund Freud’s psychoanalytic theory, which consists of the id, ego, and superego, and to examine its relevance to Indonesian language learning. This research employed a qualitative descriptive design. Data were collected through library research and note-taking techniques. The data consisted of excerpts from the novel that reflected the personality aspects of the main character. The analysis focused on identifying and interpreting the manifestations of the id, ego, and superego in Burlian’s character. The findings reveal that Burlian possesses a complex personality structure. The id is reflected in his impulsive behaviors and instinctive desires, the ego is demonstrated through his ability to adapt to reality and make rational decisions, and the superego is shown through his moral awareness and acceptance of the consequences of his actions. These three aspects indicate Burlian’s emotional and moral development throughout the story. The study concludes that the psychological portrayal of Burlian provides valuable insights into character development and can support Indonesian language learning, particularly in literature classes. The findings may serve as a learning resource to foster students’ critical thinking, reflective abilities, and character development.